Reckoning with Slavery : Gender, Kinship, and Capitalism in the Early Black Atlantic - Morgan, Jennifer L. (Jennifer Lyle) (Book collections on Project MUSE., 2021)
"Jennifer L. Morgan draws on the lived experiences of enslaved African women in the sixteenth- and seventeenth-centuries to reveal the contours of early modern notions of trade, race, and commodification in the Black Atlantic."--